2007
DOI: 10.1111/j.1538-7836.2007.02386.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal control of vascular endothelial growth factor delivery from injectable hydrogels enhances angiogenesis

Abstract: Summary. Therapeutic angiogenesis with vascular endothelial growth factor (VEGF) delivery may provide a new approach for the treatment of ischemic diseases, but current strategies to deliver VEGF rely on either bolus delivery or systemic administration, resulting in limited clinical utility, because of the short half‐life of VEGF in vivo and its resultant low and transient levels at sites of ischemia. We hypothesize that an injectable hydrogel system can be utilized to provide temporal control and appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
280
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 287 publications
(288 citation statements)
references
References 30 publications
8
280
0
Order By: Relevance
“…Polymeric systems allow for independent regulation of the localization, duration, and availability of one or more soluble factors [28][29][30], while limiting the overall quantity of drug and minimizing the potential side effects of systemic dosing. Many techniques have been developed to regulate the kinetics and distribution of soluble factors, including multiple levels of encapsulation [31] as well as noncovalently bonding the bioactive factors to peptides with a range of dissociation constants mimicking ECM immobilization of growth factors [32].…”
Section: Spatial and Temporal Control Of Morphogen And Growth Factor mentioning
confidence: 99%
“…Polymeric systems allow for independent regulation of the localization, duration, and availability of one or more soluble factors [28][29][30], while limiting the overall quantity of drug and minimizing the potential side effects of systemic dosing. Many techniques have been developed to regulate the kinetics and distribution of soluble factors, including multiple levels of encapsulation [31] as well as noncovalently bonding the bioactive factors to peptides with a range of dissociation constants mimicking ECM immobilization of growth factors [32].…”
Section: Spatial and Temporal Control Of Morphogen And Growth Factor mentioning
confidence: 99%
“…5 However, although bolus VEGF injection provided therapeutic benefit in animal studies, there was no significant improvement in clinical trials presumably due to rapid washout of the protein from bolus delivery strategies. 71 Spatiotemporal delivery of human VEGF 121 isoform within RGD-modified alginate hydrogels was shown to improve outward migration and invasion of OECs also housed within the hydrogel. 70,78 This isoform readily diffuses through the surrounding ECM unlike the VEGF 165 isoform, which binds heparin with high affinity and thus traverses more slowly.…”
Section: Delivery Of Soluble Factors For Enhanced Recruitmentmentioning
confidence: 99%
“…Alternatively, decreasing the molecular weight (MW) distribution of the polymer chains used to form the gels also permits rapid degradation, but leads to mechanical weakness. 9 Investigators have previously shown that bimodal gels created from a mixture of high MW polymers and low MW polymers (prepared via gamma irradiation 71 ) maintain mechanical stability while simultaneously providing control over degradation. 9 Such bimodal gels have been used to provide spatiotemporal control of release of multiple proangiogenic factors including VEGF, platelet-derived growth factor-BB, and S1P for therapeutic angiogenesis.…”
Section: Biomaterials Based Deployment Of Epcsmentioning
confidence: 99%
See 2 more Smart Citations